Global value chains and effective exchange rates at the country-sector level - Nikhil Patel; Zhi Wang; Shang-jin Wei (Asian Development Bank Institute (ADBI), 2017)
The real effective exchange rate (REER) is one of the most cited statistical constructs in open-economy macroeconomics. We show that the models used to compute these numbers are not rich enough to allow for the rising importance of global value chains. Moreover, because different sectors within a country participate in international production sharing in different ways, sector level variations are also important for determining competitiveness. Incorporating these features, we develop a framework to compute REER at the sector, country, and bilateral level and apply it on inter-country input-output tables to study the properties of the new measures of REER for 35 sectors in 40 countries.
Keywords: F1; F3; F4; F6; 330